Aspectos relevantes dos contratos de shopping centers - Vilhena, Felipe Barra Freitas de (2016)
This essay seeks to analyse the contracts between entrepreneurs and retailers within the shopping mall. It will address the history of this type of enterprise, as well as the characteristics and aspects that make up its complex structure and differentiate it from other types of enterprises, such as galleries and magazines. Given the peculiarities of the shopping mall contracts, there is a controversy over the legal nature of such contracts. The different doctrinal positions that qualify these contracts as typical, in the frame of the lease, atypical or linked agreements, will be a part of these study, as well as the interpretation which, it is believed, best meets the objectives of the contractors. Likewise, the more specific terms of such contracts will be examined separately, investigating the reason for its existence and the interpretation given by Brazilian Courts of Justice. The study will address the existence of different types of goodwill within the mall, and the consequence of this fact in concluding res sperata contracts, before and after the opening of the shopping mall. The work also has the scope to demonstrate the relevance of the tenant mix to the success of shopping malls and, therefore, seek to explore the importance of the role of the entrepreneur in the project planning and maintenance and constant updating of the tenant mix, in order to attract many customers to a shopping mall, always aiming to increase sales. This work will be finalized with the study of instruments, namely the eviction and denial of renewal of contracts, to be used by the entrepreneur to preserve or improve the tenant mix